Empatía ambiental (2020)
Empathy is the ability to identify yourself with another person and share their feelings, acknowledging their emotions and their problems. So what if we took this to the environmental level? When we talk about empathy we talk about emotional bonds created between human beings, but we do not think about empathy when we talk about the environment. This is how Empatía Ambiental was born, a project that seeks to develop empathic and compassionate skills towards the environment in children belonging to middle childhood (6 to 9 years), searching that they develop pro-environmental behaviors from an early age. The proposal is to achieve this through a psychoeducational intervention through an editorial piece called Bosco, el Guardián de la Naturaleza, which seeks to promote social emotional development and encourage children not only to feel empathy for the environment, but also to act in pursuit of its well-being.